Findings from an in situ Thin-section Sandwich Model for Evaluating Cariogenic and Anti-cariogenic Activity - Mellberg, J.R.; Petrou, I.D.; Grote, N.E. (Journal of dental research, 1992)
This report summarizes the findings from eight individual remineralization studies that used the thin-section sandwich model. This model uses thin sections of human enamel (or dentin) containing caries-like lesions sandwiched between sheets of thin plastic which are then implanted into the buccal surfaces of molars in removable partial mandibular dentures. Toothbrushing with a sodium fluoride-positive control dentifrice for two-week periods always produced positive remineralization of the lesions, and similar use of a placebo always produced mean mineral loss. In most studies, the difference was significant at p < 0.01. However, variation among specimens placed within an individual mouth were often large and even included cases where one lesion gained mineral while a closely adjacent lesion lost mineral. Similarly, mean mineral changes produced by an individual subject were not consistent from study to study and ranged from net demineralization in one study to net remineralization in another study. Nevertheless, mean mineral changes from all eight studies showed that all subjects produced more remineralization than demineralization when using a sodium fluoride-positive control dentifrice. Data are presented showing remineralization of thin-section lesions from a number of other fluoride and non-fluoride dentifrices and mouthrinses and showing that a product with reduced anti-caries activity (as measured by several tests) also resulted in reduced remineralization by the thin-section model.